2004
DOI: 10.2308/accr.2004.79.2.387
|View full text |Cite
|
Sign up to set email alerts
|

How Much Will Firms Pay for Earnings That Do Not Exist? Evidence of Taxes Paid on Allegedly Fraudulent Earnings

Abstract: We analyze a sample of firms accused of fraudulently overstating their earnings and examine the extent, if any, to which they paid additional income taxes on the allegedly fraudulent earnings. Based on restatements of current tax expense adjusted for the tax benefits of stock options, the evidence indicates that many firms included the overstated financial accounting income on their tax returns, thus overpaying their taxes in the process of inflating their accounting earnings. We estimate that the median firm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
155
2
11

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 330 publications
(177 citation statements)
references
References 30 publications
9
155
2
11
Order By: Relevance
“…Motivated by executive compensation arrangements and facilitated by earnings management abilities, insider trading is a predictable outcome (Cheng and Warfield, 2005). Some evidence suggests a certain degree of abuse of position is anticipated by these security markets (Liu and Yao, 2003) or, at the autopsy, a pattern of insider trading enforcement (Erickson et al, 2004). Even in a world not requiring absolute trust, markets need the assurance that some insiders will be punished (Beny, 2004).…”
Section: The Missing Elementsmentioning
confidence: 98%
“…Motivated by executive compensation arrangements and facilitated by earnings management abilities, insider trading is a predictable outcome (Cheng and Warfield, 2005). Some evidence suggests a certain degree of abuse of position is anticipated by these security markets (Liu and Yao, 2003) or, at the autopsy, a pattern of insider trading enforcement (Erickson et al, 2004). Even in a world not requiring absolute trust, markets need the assurance that some insiders will be punished (Beny, 2004).…”
Section: The Missing Elementsmentioning
confidence: 98%
“…Thus, BTDs are created. On the other hand, managers could employ conforming earnings management techniques that affect both book and tax income and thus does not alter BTDs (Erickson et al 2004). Thus, these studies based on BTDs would not be an effective method to evaluate firms that employ conforming earnings management techniques.…”
Section: Empirical Evaluation Of the Factors Attributed To Book-tax Imentioning
confidence: 99%
“…Lennox et al (2013) also found that the impact of tax reporting aggressiveness on the probability of firm with accounting fraud is negative and significant. This impact is caused by the increasing of opportunity to be monitored by tax authorities (Erickson, et al 2004). Dhaliwal et al (2004) showed that firm will tend to reduce tax avoidance measures to meet or beat analysts' forecasts earnings.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…It is done to avoid the suspicion from savvy investors, capital market authorities, and the tax authorities (Erickson, et al, 2004;Desai, 2005;Desai and Dharmapala, 2006). Erickson et al (2004) describe four potential tax treatment that can be applied by the manager when the company overstated earnings in its financial reporting. First, management may choose not to report the overstated earnings report the company and classifies tax on temporary differences between accounting standards and tax regulations.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation